The Ventral Striatum is Implicated in the Analgesic Effect of Mood Changes - Chantal Villemure; Audrey C Laferrière; M Catherine Bushnell (Pain Research and Management)
BACKGROUND: The ventral striatum, particularly the nucleus accumbens, is commonly associated with the processing of reward and positive stimuli, positive affect as well as antinociceptive processes.